2003
DOI: 10.1071/rd03045
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and chromosomes of two intersexual dasyurid marsupials

Abstract: The intersexual phenotypes of marsupials with XXY and XO chromosome constitutions imply that not all sexual dimorphisms are under the control of testicular hormones and, ultimately, the SRY gene on the Y chromosome. It has been hypothesised that there is a gene on the X chromosome that determines whether either a scrotum will form (one copy of the gene) or a pouch with teats (two copies of the gene). Here, we describe the anatomy and chromosomes of two intersexual dasyurid marsupials. One, a Dasyuroides byrnei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Its external features were described previously (Woolley and Graves, 2003). Fibroblast cell lines from skin derived from both sides of the intersex animal, as well as from normal male and female siblings, were available from this animal.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Its external features were described previously (Woolley and Graves, 2003). Fibroblast cell lines from skin derived from both sides of the intersex animal, as well as from normal male and female siblings, were available from this animal.…”
Section: Methodsmentioning
confidence: 99%
“…We reported that cells from the male side had an apparently normal female karyotype (2n = 14, XX) and cells from the female side had a female karyotype plus two extra elements (2n = 14, XX + 2B). Another dasyurid animal (Dasyuroides byrnei) with a similar phenotype, was discovered in 1967 (Woolley et al, 2003). Lymphocytes contained two cell populations, one with an apparently normal female karyotype, and the other with a female 2n = 14, XX karyotype, plus two dot-like chromosomes.…”
Section: Copyright © 2003 S Karger Ag Baselmentioning
confidence: 99%
See 2 more Smart Citations